2003
DOI: 10.1002/mpo.10322
|View full text |Cite
|
Sign up to set email alerts
|

Malawi pilot study of Burkitt lymphoma treatment

Abstract: It is possible to administer less intense and less costly multiagent chemotherapy to children with BL in a developing society with acceptable EFS rates. Adequate supportive care of the at-times associated severe toxicity must be made available to better the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 6 publications
7
68
3
Order By: Relevance
“…These findings were consistent with similar studies which concluded that there was no statistically significant association between non compliance and low per capita family income [11,12]. The level of education and knowledge of the disease of the guardians were also shown to have no statistical significance in relation to adherence which is similar to some studies where demographic factors such as level of education, knowledge of the disease and race were found to have no association with adherence [14].…”
Section: Cumulative Doses Of Doxorubicin Usedsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings were consistent with similar studies which concluded that there was no statistically significant association between non compliance and low per capita family income [11,12]. The level of education and knowledge of the disease of the guardians were also shown to have no statistical significance in relation to adherence which is similar to some studies where demographic factors such as level of education, knowledge of the disease and race were found to have no association with adherence [14].…”
Section: Cumulative Doses Of Doxorubicin Usedsupporting
confidence: 82%
“…Table 9: Cumulative doses of doxorubicin Discussion A total of nineteen patients were included in the study of which most of (68.4%) the patients were male at (n=13). This is similar to most studies done in Kenya by Mwanda, et al and similar studies done in Uganda and Malawi which showed males being more susceptible to the disease than females [9][10][11].…”
Section: Knowledge Assessmentsupporting
confidence: 78%
“…The age range of patients with BL was 2.5-13 years, with peak age of incidence in the 1st decade of life, predominantly affecting boys. BL is a common childhood malignancy in a number of African countries 21,24 . The Epstein-Barr virus is consistently found in tumour cells of BL 3 , which is endemic in East and Central Africa, where it is considered an aetiologic factor with malaria also considered a pathogenic co-factor 9,13,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Malawi pilot study of BL treatment [15] Our hypothesis was that it would be possible to improve the cure rate of eBL patients with St Jude stages I, II and III eBL, by treatment with a chemotherapy schedule that was based on the LMB 89 Group B protocol, but of reduced intensity, and by providing matching supportive care.…”
mentioning
confidence: 99%